Should gold be held under global economic policy uncertainty? - Qin, Meng; Su, Chi-Wei; Xiao, Yi-Dong; Zhang, Shuai (Journal of Business Economics and Management, 2020)
This paper investigates the ability of gold to hedge worldwide risks from the perspective of global economic policy uncertainty (GEPU). By applying the full- and sub-sample rolling-window bootstrap causality tests to analyze the dynamic interaction between GEPU and gold price (GP). It can be observed that gold can effectively hedge risks of GEPU during the Asian financial crisis, dot-com bubble and global economic crisis, but this result does not hold in non-crisis period. GEPU manifests two-way impacts on the GP in a few periods, this relationship between GEPU and GP being consistent with the hypothesis in the general equilibrium model, which states that changes in GEPU lead to the fluctuations of GP. In turn, GP has both positive and negative impacts on GEPU. In the current complex economic situation, governments and investors can consider gold to hedge risks of GEPU, especially during the economic crises.